PENGARUH SANKSI PERPAJAKAN DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK - Syafira, Erika Zahra Afifah; Nasution, R. (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2021)
The porpuse of this research is to know the impact of tax penalties and the quality of service on taxpayer’s obedience. The data that used in this research is primary data that obtained through the distribution of questionnaires to sample that represent the criteria of the population. The population of this research is taxpayer of KPP Pratama Cikarang Selatan. As for the sample of this reaserch is 100 respondents, that determined by the slovin formula. The methods of this research for validity data is used validity test and reability test. To perevent any bias of use regretion models on research, then used a classical assumption test. The analysis technique that used is multiple regression analysis. For hypothetical test in this research used the t-test that is a partial test and F-test that is a simultaneous test. The result of this research is 1. The tax penalties have a positive and significant impact on taxpayer’s obedience 2. The quality of servis have a positive and significant impact in taxpayer’s obedience. 3. The tax penalties and the quality of service have impact in taxpayer’s obedience.